Irish GDP since independence - Sean Kenny (Queen's University Centre for Economic History (QUCEH), 2024)
This paper constructs annual GDP estimates for Ireland (1924-47) to join the first complete official aggregates. The new series is deployed to revisit Ireland's economic performance in the post-independence decades. Ireland's economy grew at 1.5 per cent per annum and average living standards improved by 40 per cent. The bulk of this was due to labour productivity improvements stemming from workers moving out of agriculture. Starting in 1924 captures the civil war recovery and paints a more positive picture of the 1920s, while the traditional narrative of a "mild" Great Depression is upheld. The 1930s recovery was aided by strong contributions from services and industry, while the economy contracted by 7 per cent during the early "Emergency". Though supporting O'Rourke's view that Irish growth was not unique against European peers, the new data provide evidence of stronger convergence against UK regions. Industry contributed most to growth during the period, growing at 3.6 per cent per annum. The equivalent rate for services was 1.3 per cent, though it contributed substantially during recovery periods. Agricultural output hardly changed due to its post-war contraction. This paper joins a growing number of studies that suggest that Ireland was poorer at independence than previously believed.
Keywords: N1; N14; O4; O47; E01; 330; Historical National Accounts; interwar period; Ireland; GDP; comparative growth; regional GDP; productivity